Development Of Zakat Distribution In The Disturbance Era - Mu'adil Faizin; Suud Sarim Karimullah; Bhismoadi Tri Wahyu Faizal; Ihsan Helmi Lubis (Fakultas Syariah UIN Fatmawati Sukarno Bengkulu, 2023)
Along with the increasing number of publications in the field of digital zakat, it is necessary to study and research related to zakat management to obtain general concepts that are used as policy standards by zakat management practitioners and national zakat regulators that aim to provide knowledge about zakat management in an easy, flexible, transparent and right on target manner. This study is field research that observes actual events in society and aims to describe the state or status of a phenomenon using empirical legal research methods and an interdisciplinary approach, namely sociological and ethnographic studies. The results of this study state that the correct distribution of zakat requires an understanding of its fiqh, which is based on the arguments contained in shari'a texts that are explored through a linguistic approach (al-qowâid al-lughawiyyah) as well as an objective shari'a approach (maqâshid asy-syarî'ah). In addition, collecting zakat funds by national amil zakat agencies and institutions in Indonesia must be by the times and technology as an alternative that will make it easier for muzakkī's to meet their needs.